2009
DOI: 10.1108/00242530910936934
|View full text |Cite
|
Sign up to set email alerts
|

The world of outreach

Abstract: Purpose -The purpose of this paper is to report on the outreach activities of the Fine Arts Library at Ohio State University. Design/methodology/approach -Outreach at Ohio State is intended to have global impact, but successful outreach is often hampered by lack of partnerships, funding restrictions, and a monolithic approach to the patron. The paper reflects on each of these issues and discusses the strategies used by the Fine Arts Library to conduct outreach with user-focus and budgets in mind. Findings -The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In his study, 74% of respondents had indicated that there was no change in the budget allocation for outreach activities during last five years. Gluibizzi (2009) discusses the techniques with low-cost and high impact for outreach initiatives at Fine Arts Library, University of Ohio State.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In his study, 74% of respondents had indicated that there was no change in the budget allocation for outreach activities during last five years. Gluibizzi (2009) discusses the techniques with low-cost and high impact for outreach initiatives at Fine Arts Library, University of Ohio State.…”
Section: Literature Reviewmentioning
confidence: 99%